1995
DOI: 10.1088/0965-0393/3/4/003
|View full text |Cite
|
Sign up to set email alerts
|

A computational model for nucleation of solid-solid phase transformations

Abstract: A computational methodology for nucleation of phase hansformations in a class of gade 2. non-linearly elastic materials is presented. Nucleation is treated as an energy exbmum problem. The material is assumed to be governed by a non-linear. non-local elastic constitutive relation represented by a Landau-Ginzburg potential. The extremum problem is solved using the element-free Galerkin (m) method and a pembed Lagrangian lechnique. The m method is used because of its abflity to handle continuity of displacement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…Comparing (25) and (17), one can deduce that the present method is di erent from that proposed in Reference [19]. Although the order of (25) is identical to that of (17), the matrices K and F in (25) are di erent fromK andF in (17).…”
Section: Essential Boundary Conditionsmentioning
confidence: 76%
See 2 more Smart Citations
“…Comparing (25) and (17), one can deduce that the present method is di erent from that proposed in Reference [19]. Although the order of (25) is identical to that of (17), the matrices K and F in (25) are di erent fromK andF in (17).…”
Section: Essential Boundary Conditionsmentioning
confidence: 76%
“…It will be shown that K is also banded. After U 1 is obtained from (25), U 2 can be obtained from (22). Because the order of matrix B 2 is very low, the computational e ort required for the calculation of K and F in (26) and (27) is not signiÿcant, so that the present scheme is e cient.…”
Section: Essential Boundary Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a general framework, C 1 continuity on the primary variable is required when second-order derivatives of the primary variable appear in the variational statement. For example, in the nucleation of a solid-solid phase transformation based on an energy functional that is dependent on the strain and strain gradients [35] or in strain-gradient damage models [5], C 1 -continuous trial functions are required in the Galerkin implementation.…”
Section: Natural Neighbour Interpolantmentioning
confidence: 99%
“…[9] use a strain-based finite-element method together with nucleation theory (based on linear elasticity for evaluation a perturbed Lagrangian algorithm to study nucleation of a of the self-energy associated with nucleation and on the dilatational phase transformation for materials governed by assumption of a sharp interface with a constant interfacial a Landau-Ginzburg potential. Chu and Moran [10] use a disfree energy). The classical nucleation model [1][2][3][4] is known placement-based element-free Galerkin method, [11,12] in conto accurately represent heterogeneous nucleation behavior junction with a Landau-Ginzburg model in two dimensions, in the vicinity of equilibrium.…”
Section: Introductionmentioning
confidence: 99%